PROMOSI KESEHATAN JIWA ONLINE TOXIC RELATIONSHIP PADA REMAJA - Susanti Niman; Tina Shinta Parulian; Dahlia Sibarani (Jurnal Abdi Masyarakat, 2022)
Toxic relationships have an impact on the mental health conditions of adolescents. Toxic relationships can be avoided through increased knowledge. Mental health education online is a form of mental health promotion given to adolescents. Teenagers are the target of online mental health promotion, considering the ease of using webinar platforms. One of the tasks of adolescent development is to form mature interpersonal relationships. Mental health promotion about toxic relationships is essential for adolescents to avoid unhealthy interpersonal relationships and ultimately interfere with health. This community service activity aims to improve the knowledge and skills of adolescents in realizing healthy interpersonal relationships and preventing toxic interpersonal relationships. Activities are carried out online through media zoom. The method used is providing mental health education through lectures, leaflets about toxic relationships, discussions and questions and answers at the end of the activity. Participants also filled out the pretest and posttest. The number of participants was 43 teenagers (9% male and 91% female), aged between 14-21 years, with 95% education. In the activity results, there was a significant change in knowledge, were previously given education, the mean was 55.47, and after being given, it became the mean 77.91. Adolescents must recognize toxic relationships, not allow themselves to be in toxic interpersonal relationship situations and make efforts to prevent toxic interpersonal relationships.